Liver Transplantation Outcomes in a U.S. Multicenter Cohort of 789 Patients With Hepatocellular Carcinoma Presenting Beyond Milan Criteria. Issue 6 (23rd December 2020) - Kardashian, Ani; Florman, Sander S.; Haydel, Brandy; Ruiz, Richard M.; Klintmalm, Goran B.; Lee, David D.; Taner, C. Burcin; Aucejo, Federico; Tevar, Amit D.; Humar, Abhinav; Verna, Elizabeth C.; Halazun, Karim J.; et al.
Abstract : Background and Aims: The Organ Procurement and Transplantation Network recently approved liver transplant (LT) prioritization for patients with hepatocellular carcinoma (HCC) beyond Milan Criteria (MC) who are down‐staged (DS) with locoregional therapy (LRT). We evaluated post‐LT outcomes, predictors of down‐staging, and the impact of LRT in patients with beyond‐MC HCC from the U.S. Multicenter HCC Transplant Consortium (20 centers, 2002‐2013). Approach and Results: Clinicopathologic characteristics, overall survival (OS), recurrence‐free survival (RFS), and HCC recurrence (HCC‐R) were compared between patients within MC (n = 3, 570) and beyond MC (n = 789) who were down‐staged (DS, n = 465), treated with LRT and not down‐staged (LRT‐NoDS, n = 242), or untreated (NoLRT‐NoDS, n = 82). Five‐year post‐LT OS and RFS was higher in MC (71.3% and 68.2%) compared with DS (64.3% and 59.5%) and was lowest in NoDS (n = 324; 60.2% and 53.8%; overall P < 0.001). DS patients had superior RFS (60% vs. 54%, P = 0.043) and lower 5‐year HCC‐R (18% vs. 32%, P < 0.001) compared with NoDS, with further stratification by maximum radiologic tumor diameter (5‐year HCC‐R of 15.5% in DS/<5 cm and 39.1% in NoDS/>5 cm, P < 0.001). Multivariate predictors of down‐staging included alpha‐fetoprotein response to LRT, pathologic tumor number and size, and wait time >12 months. LRT‐NoDS had greater HCC‐R compared with NoLRT‐NoDS (34.1% vs. 26.1%, P < 0.001), even after controlling for clinicopathologic variables (hazard ratio [HR] = 2.33, P < 0.001) and inverse probability of treatment‐weighted propensity matching (HR = 1.82, P < 0.001). Conclusions: In LT recipients with HCC presenting beyond MC, successful down‐staging is predicted by wait time, alpha‐fetoprotein response to LRT, and tumor burden and results in excellent post‐LT outcomes, justifying expansion of LT criteria. In LRT‐NoDS patients, higher HCC‐R compared with NoLRT‐NoDS cannot be explained by clinicopathologic differences, suggesting a potentially aggravating role of LRT in patients with poor tumor biology that warrants further investigation.